Mulheres importantes na vida de alunos deflagradas no gênero biografia: uma prática de letramento no 9º ano do Ensino Fundamental - Aguiar, Juliana Freitas (2020)
This work aims to expand the literacy of 9th grade students from a public school in Fortaleza, culminating, after a sequence of activities that focuses on women, with the writing of the genre biography. With this, it is intended to achieve the reflection on women and contribute to a writing associated with the social practices experienced by students. For this, a sequence of activities was used and it proposed, at the end, the writing of the biography of an important woman in the students' lives. The theoretical input about literacy is based on Kleiman (2008), Street (2014) and Soares (2019). The Research on female gender was considered under the studies of Alembert (2004), Perrot (2008), Kunzler (2008) and Louro (1997). The documents that guide education in the country, “Parâmetros Curriculares Nacionais” of the Portuguese Language (1998) and “Base Nacional Comum Curricular” (2017), certify the need for the use of speech genres in the daily routine of classes. In this perspective, the theory of genre is presented in this work by Bakhtin (1997) and, in the conception of teaching, by Marcuschi (2000), (2005), (2006) and (2008). To organize our sequence of activities didactically, which was guided by Swales' genre constellation theory (2014) and important notes by Nobre and Biasi-Rodrigues (2012), the Basic Roadmap for didactic activity planning was adopted based on the genre constellation of Araújo and Zanotto (2011). The research methodology has a qualitative approach in the practice of action-research (THIOLLENT, 2011). In the sequence of activities, the genres arranged in the chain constellation contributed to the expansion of the intended literacy, which instigated the reflection about women in society and the reframing of important women in the students' lives. The analysis of the activities is related to the PCN and the BNCC, in order to verify the outlined objective.